Sharia Hotel Concept and Customer Value Effect on Customer Satisfaction - Sheila Khairana Alandri; Verinita Verinita (Integrated Journal of Business and Economics (IJBE), 2019)
Aims of this study to see the effect of the hotel sharia concept and customer value on customer satisfaction. This research was motivated by the increase of halal tourism in the world which made the majority of the Muslim population in Indonesia aware of halal lifestyle so that it became a growing trend, and this also made the people's need for products and activities according to sharia increase. Sample of this research is consumers who have stayed overnight and felt hotel facilities in sharia hotels in Padang city at least once. Data collection technique used is a non-probability sampling method with a purposive sampling approach and data collection is done by distributing questionnaires online to 190 respondents. Data analysis method uses SEM (Structural Equation Modeling) based on components or variants, which are operated through PLS applications. Results of this study are that the sharia hotel concept and customer value have a significant effect on customer satisfaction, this means that the better the concept of sharia hotels both in terms of service, interior design and financing, customer satisfaction will increase, as well as the value of customers the more value obtained by customers both from the value of quality, emotional value, price value and social value, the higher satisfaction obtained by the customer.